PENGARUH MEDIA KOMPUTER TERHADAP MINAT BELAJAR SISWA DENGAN MICROSOFT POWER POINT PADA PESERTA DIDIK KELAS IX SMPN 06 RUPAT TAHUN AJARAN 2020 - Ismah, Nurul; Sidratul Munti, Novi Yona (Jurnal Inovasi Teknik Informatika, 2021)
Learning in schools is still conventional, namely a model that uses a simple system such as lectures, discussions, and group work. In determining the learning model. Efforts to make students improve their mastery of student learning material cannot be separated from several factors. In this case, teachers who are more creative are also needed in order to attract students’ attention in learning, create a fun and interesting atmosphere so that students do not get bored and like their learning. The formulation of the problem in this study is Is there an Influence of Computer Media on Student Learning Interest with Microsoft Power Point on Students in Class Ix Smpn 06 Rupat Academic Year 2020 Rupat District, Bengkalis Regency? For this reason, the purpose of this study was to determine the effect of computer media on student learning interest with Microsoft Power Points on students in Class Ix Junior High School 06 Rupat, academic year 2020. Studying outside school with additional hours such as computer tutoring is a method of data collection to determine the effect student interest in learning. This method is done so that researchers can calculate the percentage of students’ interest in learning with computer media with students who are not interested in learning with computer media.